SYSTEMATIC REVIEW RASIONALITAS ANTIHIPERTENSI PADA PREEKLAMSIA DI BEBERAPA RUMAH SAKIT DI INDONESIA MENGGUNAKAN PENDEKATAN PRISMA - Yastin Nurfauziah; Faizal Hermanto (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2026)
Globally, preeclampsia is one of the main contributors to maternal mortality. In Indonesia, discrepancies between clinical practice and guideline recommendations for antihypertensive use in preeclampsia cases remain relatively high, potentially increasing risks for both mothers and fetuses. This study is a PRISMA-based systematic review that aims to evaluate the rational use of antihypertensive drugs in preeclampsia patients across various hospitals in Indonesia. A literature search was conducted in PubMed and Google Scholar for the period 2015–2025, identifying 76 articles, of which 11 met the inclusion and exclusion criteria. Most studies assessed three parameters of rationality—appropriate drug, appropriate indication, and appropriate dose—with mean adherence rates of 92.55%, 91.69%, and 86.73%, respectively. Nifedipine was the most commonly used first-line agent, while methyldopa was frequently used as an alternative or in combination; however, several hospitals still reported the use of drugs that are not recommended, such as candesartan. Variations in practice were mainly related to limited availability of first-line drugs and inconsistent implementation of dosing protocols, as reflected by one hospital where dose appropriateness reached only 5.3%. Overall, the use of antihypertensive therapy for preeclampsia in Indonesia is generally in line with existing guidelines; nevertheless, equitable access to essential medicines and ongoing training for healthcare workers are still needed to address therapy discrepancies arising from resource limitations.